2018
DOI: 10.1016/j.jadohealth.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mind–Body Therapies Among Young Adults Aged 18–24 Years: Findings From the 2012 National Health Interview Survey

Abstract: Young adulthood is a critical period in the life course when individuals are establishing lifestyle and health behaviors that can be enduring. Because stress is a persistent problem, and many MBTs can be helpful with management of stress and anxiety, young adult may be underutilizing these modalities. Public health and educational strategies for greater engagement in MBT among young adults are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Mindfulness, meditation, and yoga have been coined as a non-stigmatizing alternative to traditional mental health support. They are highly popular tools at tertiary education institutes and used for stress reduction, improve productivity and general mental health (7). Yoga, mindfulness, and meditation are part of a suite of interventions called mind-body interventions (8).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness, meditation, and yoga have been coined as a non-stigmatizing alternative to traditional mental health support. They are highly popular tools at tertiary education institutes and used for stress reduction, improve productivity and general mental health (7). Yoga, mindfulness, and meditation are part of a suite of interventions called mind-body interventions (8).…”
Section: Introductionmentioning
confidence: 99%
“…These studies describe the genomic and epigenetic pathways of stress, focusing on gene expression changes brought about by mind-body therapies. Despite a number of studies supporting the effectiveness of these interventions in lowering the level of stress, [ 13 , 25 , 26 , 27 , 28 ], improving well-being [ 29 , 30 , 31 , 32 ], and academic attainment in student populations [ 33 ], they may also present adverse effects and contraindications [ 34 , 35 , 36 , 37 , 38 ], especially for those individuals who are advised against mild to moderate physical exertion. In addition, mind-body therapies often require training that may be challenging to learn, and they are generally time-consuming to perform.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (Finkelstein-Fox, Park, & Riley, 2018;Gallego, Aguilar-Parra, Cangas, Rosado, & Langer, 2016;Meier & Welch, 2016;Running & Hildreth, 2017;Saoji, Mohanty, & Vinchurkar, 2017) Despite a number of studies supporting the effectiveness of these interventions in lowering the level of stress, (Gallego et al, 2016;Nanthakumar, 2018;Stillwell, Vermeesch, & Scott, 2017;Upchurch, Gill, Jiang, Prelip, & Slusser, 2018;Wang & Hagins, 2016), improving well-being (Birtwell, Williams, van Marwijk, Armitage, & Sheffield, 2019;Sarkissian, 2014;Soares & Chan, 2016;Zhang et al, 2018), and academic attainment in student populations (Bennett & Dorjee, 2016), they may also present adverse effects and contraindications. Notwithstanding the scarcity of empirical investigation on this subject, it is reported that mindfulness and meditation may induce temporary neurotic/anxiety symptoms (Dobkin, Irving, & Amar, 2012); mindful meditation, in particular, may induce psychosis, mania, or suicidal ideation especially in those with prior psychiatric morbidity (Wielgosz, Goldberg, Kral, Dunne, & Davidson, 2019); the autogenous training is contraindicated for those who suffer from a number of medical and/or mental conditions, for example, hypertension and psychosis (Brancaleone, 2010); yoga may not be recommended for those who suffer from arthritis (Dobkin et al, 2012); guided imagery may trigger post-traumatic stress symptom in patients with a history of previous emotional, sexual, or physical abuse (American Academy of Pediatrics, 2016); and qigong is contraindicated for those who have suffered from mental illness or severe consumptive disease, cerebrovascular disease, and severe cardiovascular, liver, kidney, gastrointestinal and hematological diseases, and musculoskeletal system diseases (Guo et al, 2018).…”
mentioning
confidence: 99%